2018
DOI: 10.1371/journal.pone.0194866
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic characteristics and zearalenone-removal ability of a Bacillus licheniformis strain

Abstract: Zearalenone (ZEN) is a mycotoxin produced by Fusarium species, which is one of the main animal feed contaminants causing reproductive disorders in livestock. The aim of this study was to evaluate the probiotic characteristics and ZEN removal ability of a Bacillus licheniformis strain CK1. The probiotic properties, including acidic tolerance, bile salt tolerance, adherence capability, and anti-pathogenic activities of CK1 were evaluated. CK1 survived after incubation at pH 2.0 or 3.0 for 3 h, grew well in LB br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…This is the first report, to our best knowledge, to evaluate the probiotic characteristics of the LAB strains isolated from wild boar. The bile salt in the duodenum and the acid condition of the stomach has been reported as the biggest obstacles to the survival of LAB in the GI tract of host (44). In the study, the different levels of resistance to bile salt of five isolates may depend on the expression of bile resistance-related proteins in the LAB cells (45).…”
Section: Discussionmentioning
confidence: 92%
“…This is the first report, to our best knowledge, to evaluate the probiotic characteristics of the LAB strains isolated from wild boar. The bile salt in the duodenum and the acid condition of the stomach has been reported as the biggest obstacles to the survival of LAB in the GI tract of host (44). In the study, the different levels of resistance to bile salt of five isolates may depend on the expression of bile resistance-related proteins in the LAB cells (45).…”
Section: Discussionmentioning
confidence: 92%
“…Many microorganisms capable of degrading mycotoxins have been identified in the field of detoxification of mycotoxins. For instance, it has been confirmed that in the process of mycotoxin decontamination, the microbial cell wall has a good adsorption effect on ZEN (such as yeast [ 36 ], Lactobacillus plantarum [ 22 ]), and the microbial secretase has an efficient degradation effect on ZEN (such as Bacillus subtilis [ 24 ], Bacillus licheniformis [ 37 ], Bacillus amyloliquefaciens [ 38 ], and Rhodococcus pyridinivorans K408 [ 39 ]). In the pre-test of the ZEN detoxification study, we isolated and identified a new bacterial strain ( Bacillus velezensis A2) for the ZEN decontamination strategy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZEA reduction by Bacillus licheniformis strain CK1 was over 70% (with 5 µg ml −1 ) at 37 • C and pH 7.0, and strain CK1 removed more than 65% of ZEA in the pH range 2.5-8.0 or at temperatures from 4 to 42 • C. After five washes, CK1 cells retained over 30% of the initially bound ZEA. These results indicate that CK1 effectively removed ZEA and for these reasons may be recommended as a future feed additive to reduce or eliminate this mycotoxin [237]. It should be noted that toxin concentration reduction by means of microbiological binding can highly vary and depends on the strain of the microorganism and the physiological state of cells [203], as well as on environmental conditions [229].…”
Section: Biological Methodsmentioning
confidence: 99%